Solve lnx + ln(x-3) = 0 So far my working is e^(lnx) + e^(ln(x-3)) = e^0 x + (x-3) = 1 and so on But this leads me to the incorrect solution. Where did I go wrong?
Follow Math Help Forum on Facebook and Google+
Originally Posted by hymnseeker e^(lnx) + e^(ln(x-3)) = e^0 Where did I go wrong?
You can't do what you did. What you can do is
How foolish of me to miss that. Thanks again.
Originally Posted by hymnseeker Solve lnx + ln(x-3) = 0 So far my working is e^(lnx) + e^(ln(x-3)) = e^0 x + (x-3) = 1 and so on But this leads me to the incorrect solution. Where did I go wrong? Hello hymnseeker, Try this:
View Tag Cloud